2009
DOI: 10.1007/s12640-009-9046-9
|View full text |Cite
|
Sign up to set email alerts
|

The ANKK1 Kinase Gene and Psychiatric Disorders

Abstract: The TaqIA single nucleotide polymorphism (SNP, rs1800497), which is located in the gene that codes for the putative kinase ANKK1 (ANKK1) near the termination codon of the D2 dopamine receptor gene (DRD2; chromosome 11q22-q23), is the most studied genetic variation in a broad range of psychiatric disorders and personality traits. A large number of individual genetic association studies have found that the TaqIA SNP is linked to alcoholism and antisocial traits. In addition, it has also been related to other con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 96 publications
1
66
0
Order By: Relevance
“…Tables 2 and 3 below provide brief overviews of studies reported recently at these sites. Regarding the phenotype of psychopathy, Ponce and colleagues reported on polymorphisms at TaqIA of ANKK1, near DRD2, finding an association between the Aþ genotype and elevated factor I scores on the PCL-R (Ponce et al, 2008(Ponce et al, , 2003(Ponce et al, , 2009). Fowler and colleagues used the PCL-YV in a sample of ADHD affected subjects aged 12-19 years and looked at correlations with MAOA, 5HTTLPR, and COMT (Fowler et al, 2009).…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…Tables 2 and 3 below provide brief overviews of studies reported recently at these sites. Regarding the phenotype of psychopathy, Ponce and colleagues reported on polymorphisms at TaqIA of ANKK1, near DRD2, finding an association between the Aþ genotype and elevated factor I scores on the PCL-R (Ponce et al, 2008(Ponce et al, , 2003(Ponce et al, , 2009). Fowler and colleagues used the PCL-YV in a sample of ADHD affected subjects aged 12-19 years and looked at correlations with MAOA, 5HTTLPR, and COMT (Fowler et al, 2009).…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…For a long time, Taq1A was thought to belong to the DRD2 gene and it was studied that way [8-11]. Taq1A is one of the most studied genetic variations in a wide range of psychiatric disorders and it is also linked to alcoholism and antisocial traits [20]. However, today it is well known that Taq1A belongs to the ANKK1 gene, located in exon 8, adjacent to DRD2 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, there are several avenues implicating epigenetic mechanisms in pathological impulsive behavior found in neuropsychiatric disorders that link not only serotonergic and dopaminergic (Ponce et al, 2009) systems, but also MAO-activity and COMT (Hoenicka et al, 2010) genes and even Neuropeptide Y gene (Lesch et al, 2011) in the disease etiopathogenesis. As yet, one may only assume that the relative 'weakness' or 'strength' of the forces inducing epigenetic modulations of future genomes that influence impulsiveness may regulate outcomes of linkage studies.…”
Section: Epigenetic Implications Modulating Impulsiveness: a Case Formentioning
confidence: 99%